Spatiotemporal response of neuronal networks to time-dependent spectral features - Balenzuela, P. (2007)
In this work, we analyze the behavior of a neuronal network when it is stimulated by a synaptic train current with variable frequency. Using the fact that resonat (type II) neurons have a preferred input frequency, we constructed a network formed by two groups of neurons, each one responding to a different eigenfrequency. We show than even though every neuron is locally connected with neighbors of both groups, only those properly tuned to the input frequency fire synchronically with the incoming signal. In this sense, given a fixed sized network of heterogeneous neurons different subsets respond to the stimulus depending on its frequency. © 2007 American Institute of Physics.